Whose Bible is it? : a history of the Scriptures through the ages - Pelikan, Jaroslav, 1923-2006. (USA: Penguin Group, 2005)
No book has been more pored over, has been the subject of more commentary and controversy, or had more influence not only on our religious beliefs but also on our culture and language than the Bible. And certainly no book has been as widely read. But how did the Bible become the book we know it to be? This history of the Bible written by a major historian of theology, the author takes the reader through the Bible's evolution from its earliest incarnation as oral tales to its modern existence in various configurations and translations. From the earliest Hebrew texts and the Bible's appearance in Greek, then Latin, he explores the canonization of different Bibles and why certain books were adopted or rejected by certain religions and sects, as well as the development of the printing press, translation into modern languages, and the varying schools of critical scholarship.
The Bible, the whole Bible, and nothing but the Bible? -- The God who speaks -- The truth in Hebrew -- Moses speaking Greek -- Beyond written Torah : Talmud and continuing revelation -- The law and the prophets fulfilled -- Formation of a second Testament -- The peoples of the Book -- Back to the sources -- The Bible only -- The Canon and the critics -- A message for the whole human race -- The strange new world within the Bible -- Alternative canons of the Tanakh/Old Testament -- New Testament.
Includes bibliographical references (pages 257-274).
Keywords: Bible -- History